2009
DOI: 10.4049/jimmunol.0801468
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIA and FcγRIIIB Mediate Nuclear Factor Activation through Separate Signaling Pathways in Human Neutrophils

Abstract: Receptors for IgG Abs (Fcγ receptors) are capable of triggering diverse cell responses in leukocytes. In neutrophils, two Fcγ receptors, namely FcγRIIA and FcγRIIIB, are constitutively expressed. The signaling pathways that regulate FcγRIIA-mediated phagocytosis have been relatively well described. However, the different signaling pathways that lead to NF activation after engagement of each Fcγ receptor have only been partially described. To address this problem, neutrophils were stimulated by cross-linking se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Human neutrophils express the activating Fc␥RIIA and the glycophosphoinositol-linked Fc␥RIIIB, and human IgG1 is known to bind to the former with very high affinity (6). Furthermore, Fc␥RIIIB cross-linking does not induce nuclear migration or Erk or MEK, suggesting that these two receptors mediate human IgG1 signaling through different pathways (13). Unexpectedly, these assays also indicated that human IgG3 may be a poor inducer of respiratory bursts despite possessing the highest affinity for Fc␥Rs of all of the human IgG subclasses (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…Human neutrophils express the activating Fc␥RIIA and the glycophosphoinositol-linked Fc␥RIIIB, and human IgG1 is known to bind to the former with very high affinity (6). Furthermore, Fc␥RIIIB cross-linking does not induce nuclear migration or Erk or MEK, suggesting that these two receptors mediate human IgG1 signaling through different pathways (13). Unexpectedly, these assays also indicated that human IgG3 may be a poor inducer of respiratory bursts despite possessing the highest affinity for Fc␥Rs of all of the human IgG subclasses (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…Crosslinking of hFcγRIIA by IgG ICs results in the phosphorylation of ITAM tyrosine residues, followed by recruitment and activation of the tyrosine kinase Syk. This leads to calcium mobilization, activation of MAPK pathways, activation of NF-κB, and inflammatory cell activation (11). Two codominantly expressed alleles of hFcγRIIA differ by an arginine or a histidine at amino acid position 131 and by their affinity for hIgG2.…”
Section: Introductionmentioning
confidence: 99%
“…ITAM phosphorylation permits docking of signaling proteins to the receptor molecule, which then initiates a cascade of events promoting inflammatory responses. The type of inflammatory response initiated varies according to the specific FcGR undergoing regulatory phosphorylation (14,15) and whether the ITAM motif resides in the cytoplasmic tail of the FcGR or in an associated protein (24,25). Tyrosine protein kinase also regulates the inhibitory FcGR2B signals via an immunoreceptor tyrosine-based inhibitory (ITIM) motif (Figure 2).…”
Section: Tyrosine Protein Kinase Inhibition and Isoflavonesmentioning
confidence: 98%